PENDIDIKAN AKIDAH MENURUT PAHAM AHLUSUNAH WAL JAMAAH - HS Prodjodijoro (Jurnal Penelitian Humaniora, 2001)
Abstract This study was an educational research with a library research model, focusing on the belief education according to the concept of Ahlus Sunah Wal Jamaah. This writing observed accurately the meaning of Ahlus Sunah Wal Jamaah, disagreement among Moeslims resulting from political factors, rules (fiqih) and belief, and the historical recitation on the belief of Ahlus Sunah Wal Jamaah started by the disagreement between Al Imam Al Bashary (as a teacher) and Washil bin Atho’ (as a student) concerning with a Moeslim conducting a big sinful deed, whether he/she is a Moeslim or infidel(unbeliever). This argument based on Al-Quran and Al-Hadist was called Ahlus Sunah Wal Jamaah, while the other was not belong to that concept. This discussion come to Imam Al Asyari (student) debated with his teacher Al Juba’I regarding to “ Shalah and Ashlah” from the thought of Al-Asy’ari and the followers. This was the concept called the belief of Ahlus Sunah Wal Jamaah. The the term experience the broadening of meaning, the method development and the topic of discussion, the way of using argumentation, related to its followers. Keywords: belief education Ahlus Sunah Wal Jamaah